2019
DOI: 10.1038/s41467-019-12296-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of the myeloma bone-lining niche reveals BMP signalling inhibition to improve bone disease

Abstract: Multiple myeloma is an incurable, bone marrow-dwelling malignancy that disrupts bone homeostasis causing skeletal damage and pain. Mechanisms underlying myeloma-induced bone destruction are poorly understood and current therapies do not restore lost bone mass. Using transcriptomic profiling of isolated bone lining cell subtypes from a murine myeloma model, we find that bone morphogenetic protein (BMP) signalling is upregulated in stromal progenitor cells. BMP signalling has not previously been reported to be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 64 publications
(84 reference statements)
3
35
0
Order By: Relevance
“…Prostate cancer cells as well as the stroma of the bone marrow are supported by BMP signaling to drive bone metastases (65). A recent study showed that inhibition of BMP signaling improved bone health without increasing tumor growth in the bones of a multiple myeloma mouse model (66). Our findings support further investigation into how myeloid BMP drives tumor progression, and how to target BMP signaling in the metastatic tumor microenvironment.…”
Section: Discussionsupporting
confidence: 73%
“…Prostate cancer cells as well as the stroma of the bone marrow are supported by BMP signaling to drive bone metastases (65). A recent study showed that inhibition of BMP signaling improved bone health without increasing tumor growth in the bones of a multiple myeloma mouse model (66). Our findings support further investigation into how myeloid BMP drives tumor progression, and how to target BMP signaling in the metastatic tumor microenvironment.…”
Section: Discussionsupporting
confidence: 73%
“…To further demonstrate that RIP1 promoted the expression of BMP7, the concentration of BMP7 in the cultural supernatant of chondrocytes was determined before and after RIP1 overexpression, the result showed that RIP1 increased secreted BMP7 level in a dose-dependent manner (Figure 8B). As BMPs play pivotal roles in the regulation of bone induction, maintenance and repair, we also performed Alizarin red staining to reveal the formation of calcium deposits in chondrocytes, which are indicative of ossification (Lowery and Rosen, 2018;Gooding et al, 2019;Wei et al, 2020). As expected, RIP1-overexpressing chondrocytes showed positive reaction with Alizarin red while control cells were negative, indicating that RIP1 indeed induces endochondral ossification, a crucial process during OA progression (Figure 8C).…”
Section: Identification Of Bmp7 As the Target Of Rip1 In Chondrocytesmentioning
confidence: 62%
“…However, the wealth of molecular information obtained from a bone biopsy outweighs the procedural and technical risks. In a multiple myeloma mouse model, transcriptomic profiling of the bone microenvironment identified bone morphogenetic protein signaling as a targetable approach for treatment of myeloma TIBD 75 . Based on the cellular and molecular composition of an individual patient's TIBD, appropriate therapeutics can be selected to improve patient outcomes.…”
Section: New Horizons For Metastatic Bonementioning
confidence: 99%